The Implementation of the Free Vehicle Inspection Fee (KIR) Program at the Motor Vehicle Testing Unit (UPTD PKB) Wiyung, Surabaya City Transportation Agency - Habiba Dwi Wulandari; Suci Megawati; Indah Prabawati; M. Noer Falaq Al Amin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Free Vehicle Roadworthiness Test Retribution Program is a policy of the Surabaya City Government in the transportation sector that aims to increase vehicle owner compliance in conducting vehicle roadworthiness tests, support traffic safety, and improve the quality of public services, implemented by the Wiyung Motor Vehicle Testing Unit (PKB) of the Surabaya City Transportation Agency through the elimination of regional levies. This study aims to describe the implementation of the policy using a descriptive qualitative approach through interview, observation, and documentation techniques, and analyzed using Van Meter and Van Horn's policy implementation theory which includes policy measures and objectives, resources, characteristics of implementing organizations, attitudes of implementers, inter-organizational communication, and social, economic, and political conditions. The results of the study indicate that the implementation of the Free Vehicle Roadworthiness Test Retribution Program has not been running optimally, marked by the community not fully understanding the objectives of the policy who still perceive the program as a free service, limited human resources and infrastructure, and suboptimal policy socialization, even though policy implementers have shown commitment in implementing the program. Therefore, it is necessary to increase socialization, strengthen supervision, and optimize resources so that policy implementation can run more effectively and sustainably.